Cost-effectiveness of use of 20-valent pneumococcal conjugate vaccine among adults in Germany - Felicitas Kühne; Katharina Achtert; Franziska Püschner; Dominika Urbanski-Rini; Juliane Schiller; Ernestine Mahar; Josephine Friedrich; Mark Atwood; Ralf Sprenger; Jeffrey Vietri; Christof von Eiff; Christian Theilacker (Expert Review of Vaccines, 2023)
Objectives Despite national recommendations for use ofpneumococcal vaccines, rates of community-acquired pneumonia (CAP) and invasivepneumococcal disease (IPD) remain high in Germany. New pneumococcal conjugatevaccines (PCVs) with expanded coverage have the potential to reduce thepneumococcal disease burden among adults. Methods Using a Markov model, we evaluated the lifetimeoutcomes/costs comparing 20-valent PCV (PCV20) with standard of care (SC)vaccination for prevention of CAP and IPD among adults aged ≥60 years and at-riskadults aged 18-59 years in Germany. PCV20 also was compared with sequential vaccinationwith 15-valent PCV (PCV15) followed by (→) PPSV23 in a scenario analysis. Results Over the course of a lifetime (82 years), use of PCV20vs. SC would prevent 54,333 hospitalizations, 26368 outpatient CAP cases, 10946disease-related deaths yield 74,694 additional life-years (LYs), while loweringtotal medical costs by 363.2 M €. PCV20 remained cost saving (i.e. dominant)versus SC even in numerous sensitivity analyses, including a sensitivityanalysis assuming moderate effectiveness of the SC pneumococcal polysaccharidevaccine against noninvasive pneumococcal CAP. In several scenario analyses anda probabilistic sensitivity analysis, PCV20 was also cost-saving compared toPCV15→PPSV23 vaccination. Conclusions One dose of PCV20 among adults aged ≥60 years andadults aged 18-59 years with moderate- and high-risk conditions wouldsubstantially reduce pneumococcal disease, save lives, and be cost savingcompared with SC.